2010
DOI: 10.1021/jz1014339
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Local Structure of Graphene Oxide

Abstract: A study of the local structure of graphene oxide is presented. Graphene oxide is understood to be partially oxidized graphene. Absorption peaks corresponding to interlayer states suggest the presence of pristine graphitic nanoislands in graphene oxide. Site-projected partial density of states of carbon atoms bonded to oxygen atoms suggests that the broadening of the peak due to interlayer states in the carbon K-edge spectrum of graphene oxide is predominantly due to formation of epoxide linkages. Density funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 30 publications
6
85
0
1
Order By: Relevance
“…The peak at 540.1 eV is usually assigned to hydroxyl groups, however, the contribution of the other oxygen functionalities, such as carbonyl, carboxylic and epoxides is also suggested. 25 At the same time, the peak at 535.8 eV shifted to lower energy of 534.5 eV, which is rather similar to that of the peak (533.6 eV) assigned to state of C-O from epoxide. 26 Based on these results and a small interlayer spacing of TRGO900, it would be better to think that the hydroxyl groups on the GO layers are more preferably removed, while some C-O and C=O containing groups such as pyrone, pyran, furan and quiones 27 still remained within the carbon layers of TRGO900.…”
Section: Resultssupporting
confidence: 64%
“…The peak at 540.1 eV is usually assigned to hydroxyl groups, however, the contribution of the other oxygen functionalities, such as carbonyl, carboxylic and epoxides is also suggested. 25 At the same time, the peak at 535.8 eV shifted to lower energy of 534.5 eV, which is rather similar to that of the peak (533.6 eV) assigned to state of C-O from epoxide. 26 Based on these results and a small interlayer spacing of TRGO900, it would be better to think that the hydroxyl groups on the GO layers are more preferably removed, while some C-O and C=O containing groups such as pyrone, pyran, furan and quiones 27 still remained within the carbon layers of TRGO900.…”
Section: Resultssupporting
confidence: 64%
“…Potential applications of GO in water desalination and purification has also been explored [19][20][21][22]. The unique structural features [23], high mechanical strength [24] and the atomic-level thickness of GO have been exploited to fabricate an extremely thin membrane with controlled pore size and high flux [19,20,25,26]. Molecular simulation have shown the impermeability to salt molecules along with high pure water flux [26], and GO nanosheets have demonstrated excellent antifouling properties [27].…”
Section: Introductionmentioning
confidence: 99%
“…edge NEXAFS database in the literature is not rich enough to deconvolute and assign all the peaks41,[49][50][51][52][53] . Upon judicious review of the available literature we have deconvoluted the peaks as shown inFigure 8 (a).…”
mentioning
confidence: 99%